Description of smartphone addiction in adolescents SMP HKBP Padang Bulan Medan 2022 - Sinurat, Samfrianti; Pakpahan, Rotua; Nainggolan, Romauli (Institute of Accounting Research and Novation (IARN), 2023)
Smartphone addiction as an attachment to a smartphone accompanied by a lack of control and has a negative impact on students. The term smartphone addiction is a behavior of attachment or addiction to a smartphone which is likely to become a social problem such as withdrawal, and difficulties in performing daily activities or as a disorder of impulse control against one's self. This study aims to determine the description of smartphone addiction in HKBP Padang Bulan Medan Middle School Adolescents in 2022. This type of research uses descriptive research. The sampling technique in this study used a total sampling of 80 respondents. The instrument used is the Smartphone Addiction Questionnaire. The results showed that of the 80 respondents, the majority of students who had severe smartphone addiction were 45 respondents (56.25%), and a mild minority of 5 (6.25%).